SERVICE SATISFACTION OF ARRIVAL REPORT LETTER (STBLKK) AT THE BUNGUS OCEANIC FISHING PORT - Safitriani Safitriani; Hasanah Hasanah (Universitas Mataram, 2024)
Bungus oceanic fishing port (PPS) Bungus was one of the fishing ports in Indonesia. Bungus fishing port conducts mooring activities. The mooring activity is that fishermen moor their ships at a port and require a proof of arrival report letter (STBLKK). The purpose of this study was to determine service procedure and the satisfaction of STBLKK services at PPS Bungus. Implementation of SOP at service procedure at Bungus Ocean Fishing Port is that every fishing vessel that will come or moor / dock at the dock is required to report and make a proof of arrival report letter, the issuance of STBLKK at Bungus Ocean Fishing Port is in accordance with existing procedures. The questionnaire results show that the five questions posed to the ship's management show very suitable results for convenience, speed, satisfaction, courtesy, and security services. The implementation of the service of issuing proof of ship arrival report (STBLKK) is very suitable based on the value of the Community Satisfaction Index (SMI) A, which is 98.5. Ship management satisfaction with STBLKK service procedures is very good.